Numerical modeling of the gas breakdown development in the space–charge layer inside the nozzle of a transferred arc torch - Mancinelli, Beatriz Rosa (2012)
Double–arcing is a phenomenon that occurs when a transferred arc, flowing inside an electrically insulated nozzle, breaks into two separate arcs: one that connects the cathode with the nozzle, and another that connects the nozzle with the anode. Experimental evidence suggests that the reason for double–arcing is a Townsend like breakdown occurring in the thin space–charge layer, which separates the plasma from the metallic nozzle, due to the high voltage drop across it. Breakdown phenomena in a gas between metallic electrodes have been extensively studied; however the present case involves breakdown of a high–temperature gas between one electrode (the nozzle) and a plasma boundary. A 1–D model of the gas breakdown development in the space–charge layer contiguous to the nozzle of a cutting arc torch operated with oxygen is reported. The dynamics of the discharge is analyzed. The kinetic scheme includes processes of ionization of heavy particles by electron impact, electron attachment, electron–ion recombination and ion–ion recombination.